Kaposi's sarcoma herpesvirus activates the hypoxia response to usurp HIF2α-dependent translation initiation for replication and oncogenesis - Méndez Solís, Omayra (2021)
Kaposi's sarcoma herpesvirus (KSHV) is an angiogenesis-inducing oncovirus whose ability to usurp the oxygen-sensing machinery is central to its oncogenicity. By upregulating the hypoxia-inducible factors (HIFs), KSHV reprograms infected cells to a hypoxia-like state, triggering angiogenesis. Here we identify a link between KSHV replicative biology and oncogenicity by showing that KSHV's ability to regulate HIF2α levels and localization to the endoplasmic reticulum (ER) in normoxia enables translation of viral lytic mRNAs through the HIF2α-regulated eIF4E2 translation-initiation complex. This mechanism of translation in infected cells is critical for lytic protein synthesis and contributes to KSHV-induced PDGFRA activation and VEGF secretion. Thus, KSHV regulation of the oxygen-sensing machinery allows virally infected cells to initiate translation via the mTOR-dependent eIF4E1 or the HIF2α-dependent, mTOR-independent, eIF4E2. This “translation initiation plasticity” (TRIP) is an oncoviral strategy used to optimize viral protein expression that links molecular strategies of viral replication to angiogenicity and oncogenesis.